Prognostic Value of Peripheral Blood nCD64 Index, mHLA-DR, and CD14+monocyte Percentage in Different Infection Status in COVID-19 Patients - Zhu M; Cheng J; He L; Li C; Shi B; Jin M; Yu J; Huang J (Journal of Inflammation Research)
Mingli Zhu,1,* Jianghao Cheng,1,2,* Lingyan He,1,* Chaodan Li,1 Bin Shi,1 Meitong Jin,1 Jianhua Yu,3 Jinsong Huang3 1Open Laboratory, Hangzhou Xixi Hospital Affiliated to Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2Laboratory Medicine, Zhejiang Cancer Hospital, Hangzhou, Zhejiang, People’s Republic of China; 3Department of Infectious Diseases, Hangzhou Xixi Hospital Affiliated to Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianhua Yu, Email yujhmc@126.com Jinsong Huang, Email huangjinsongyz@126.comObjective: To explore the value of the neutrophil CD64 (nCD64) index, monocytic HLA-DR (mHLA-DR), and the percentage of CD14+ monocytes in the prognosis of Coronavirus disease 2019 (COVID-19).Methods: Fifty-seven COVID-19 patients from December 2022 to November 2023 were divided into two groups: non-severe group (mild or moderate cases) and severe group (severe or critical cases). Among them, 17 patients were deceased. Flow cytometry was employed to detect the levels of nCD64 index, mHLA-DR, and CD14+monocyte percentage in blood. The receiver operating characteristic (ROC) curve was used to evaluate the predictive value of mHLA-DR, nCD64 index, and CD14+ monocyte percentage for COVID-19 prognosis.Results: The expression levels of mHLA-DR and the percentage of CD14+ monocytes in non-severe COVID-19 patients were significantly higher than those in severe and deceased patients (P < 0.05). In contrast, the nCD64 index in non-severe patients was significantly lower than that in severe and deceased patients (P< 0.05). The expression level of mHLA-DR and the percentage of CD14+ monocytes in deceased patients were significantly lower than those in surviving patients (P< 0.001), while the nCD64 index level in surviving patients was significantly lower than that in deceased patients (P< 0.001). The area under the curve (AUC) for the nCD64 index, mHLA-DR and the percentage of CD14+ monocytes were 0.850, 0.779 and 0.871, respectively. Patients with CD14+ monocyte percentage > 4.9%, mHLA-DR value > 16720.5, and nCD64 index < 5.87 had a good prognosis value (P < 0.05).Conclusion: The nCD64 index, mHLA-DR level, and percentage of CD14+ monocytes may serve as biomarkers for predicting clinical outcomes in COVID-19 patients.Keywords: nCD64 index, mHLA-DR, CD14+ monocyte percentage, COVID-19